2022
DOI: 10.1097/ta.0000000000003577
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and pulmonary complications in emergency general surgery patients with COVID-19: A large international multicenter study

Abstract: The outcomes of emergency general surgery patients (EGS) having COVID19 are unknown. Our study across 52 countries demonstrates that COVID19 patients undergoing EGS have higher mortality and pulmonary complications especially in the presence of preoperative respiratory findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 19 publications
0
3
1
1
Order By: Relevance
“…We demonstrated an increased risk of 30-day adverse events in COVID-19-positive patients undergoing hip and knee arthroplasty and trauma surgery. While there appears to be consensus on increased risk of perioperative complications in trauma surgery in COVID-19-positive patients, 16 , 27 , 44 , 45 our results with regard to joint arthroplasty are in contrast to some recent reports arguing COVID-19 positivity does not significantly increase risk of respiratory, infectious, cardiac, and thromboembolic complications. 46 , 47 These differences may again be explained by the quality and size of studied databases and retrospective nature of analyses.…”
Section: Discussioncontrasting
confidence: 99%
“…We demonstrated an increased risk of 30-day adverse events in COVID-19-positive patients undergoing hip and knee arthroplasty and trauma surgery. While there appears to be consensus on increased risk of perioperative complications in trauma surgery in COVID-19-positive patients, 16 , 27 , 44 , 45 our results with regard to joint arthroplasty are in contrast to some recent reports arguing COVID-19 positivity does not significantly increase risk of respiratory, infectious, cardiac, and thromboembolic complications. 46 , 47 These differences may again be explained by the quality and size of studied databases and retrospective nature of analyses.…”
Section: Discussioncontrasting
confidence: 99%
“… 28 , 29 In contrast, another study focusing on patients undergoing select emergency general surgery procedures found that the higher risk of 30-day mortality and pulmonary complications is only notable in patients who had preoperative respiratory clinical or radiological findings of SARS-CoV-2 infection. 30 …”
Section: Discussionmentioning
confidence: 99%
“… 9 , 10 , 27 , 28 , 29 , 30 In agreement with this analysis, active COVID-19 infection in patients undergoing urgent or emergent surgical procedures appears to confer an increased risk of perioperative morbidity and mortality. 31 , 32 , 33 , 34 Indeed, Knisely and colleagues' 33 recent examination of COVID-19 patients demonstrated that those undergoing urgent and emergent surgical procedures were at increased risk of severe complications regardless of preoperative American Society of Anesthesiologists category, with a reported risk ratio for death in active COVID-19 patients of 55.00 for those undergoing urgent surgical procedures. These findings have been echoed by other large cohort analyses.…”
Section: Discussionmentioning
confidence: 99%
“…These findings have been echoed by other large cohort analyses. 31 , 32 , 34 Nonelective coronary bypass in the setting of COVID-19 infection poses a unique challenge to cardiac surgeons not only for the inherent risks of an urgent or emergent procedure, but also for the confounder of a significant active respiratory illness. This study highlights the increased risks associated with nonelective CABG in COVID-19 active patients and suggests careful consideration should be given to the management of these patients to optimize outcomes.…”
Section: Discussionmentioning
confidence: 99%